RATIO LANCAR DAN RATIO HUTANG ATAS AKTIVA TERHADAP MARGIN LABA BERSIH BISNIS SEKTOR MAKANAN DAN MINUMAN YANG TERCATAT DI BURSA EFEK INDONESIA TAHUN 2018 – 2022 - Yuslinda Nasution; Noviarti; Damai Yanti Sirait (Jurnal Satya Mandiri Manajemen dan Bisnis, 2024)
This study seeks to examine the impact of the current ratio (CR) and the debt to assets ratio (DAR) on the net profit margin (NPM). It employs a quantitative approach and explanatory research methodology to elucidate the relationships or effects between these variables. Sampling was performed using purposive sampling, and the analysis relies on secondary data sourced from the annual financial statements of food and beverage companies listed on the IDX from 2018 to 2022. The study utilizes multiple regression analysis, with CR and DAR serving as the independent variables and NPM as the dependent variable. The findings indicate that for food and beverage companies listed on the IDX during the 2018–2022 period, the current ratio (CR) negatively and significantly affects the net profit margin (NPM). Similarly, the debt to assets ratio (DAR) also has a negative and significant impact on NPM. This research provides valuable insights into the effects of CR and DAR on NPM, contributing to the field of economic science. Additionally, it offers a foundation for further studies, particularly those exploring financial performance in publicly traded companies.